HOW PRINCIPAL BRANDING SHAPES INSTITUTIONAL REPUTATION: INSIGHTS FROM SMPN 1 MEGALUH - Sasqia Dwi Kurniawati; Hilyah Ashoumi; M Kris Yuan Hidayatulloh; Irwan Ahmad Akbar (Jurnal Manajemen Pendidikan, 2026)
This study aims to describe the role of school principal branding in enhancing institutional image at SMPN 1 Megaluh through a descriptive qualitative approach, the descriptive qualitative approach is intended to describe the findings obtained after the research. This research method is carried out in depth through interviews with several sources, observations, and documentation. The findings reveal that the principal acts as a leader, motivator, innovator, and facilitator who actively develops a branding strategy rooted in local character, such as the use of the school logo and the slogan “SEMANGKA” (Spirit of Learning and Creating), professional utilization of social media, and empowerment of teachers, students, and the community in implementing agrarian-based school programs. This strategy not only strengthens the school’s identity but also increases public trust, as evidenced by parent involvement, growing digital presence, and the emergence of a positive perception regarding the school’s educational quality. The research matrix indicates a significant positive impact on the formation of a strong and authentic institutional image, achieved through the integration of branding into all managerial and learning aspects of the school.